Pengaruh Kohesivitas Kelompok dan Sosio Demografi terhadap Partisipasi Anggota Kelompok Tani di Desa Batur, Kecamatan Getasan, Kabupaten Semarang - Aji, Bangkit Permata; Mariyono, Joko; Prayoga, Kadhung (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Cohesiveness and sociodemographics are important in determining the participation of members in the village group to achieve the goal of the farm group itself. The research aims to analyze the influence of the cohesiveness of the group and socio-demographics (age, education, experience, and number of family members) on the involvement of members of the rural group. The locations of the research are Tani Tranggulasi and Bangkit Merbabu Group, Batur Village, Getasan District, and Central Java District. The research method used was census, which took the entire peasantry group of 85 people as respondents. Data collection was carried out through interviews with questionnaires for primary data, observations, and documentation for secondary data. The method of analysis used was double linear regression analysis with the help of SPSS in data processing. The results shows that independent variables have a real combined influence on dependent variables. It means that cohesiveness, age, education, experience, and the number of family members have a collective impact on the participation of the peasant group. In part, cohesiveness, age, and experience influenced the participation of the peasant group members, while education and the number of family members did not restrict the membership of the rural group. The results of this study can be used as a learning experience for farmer groups and as a reference for the government in implementing programs in farmer groups. Given that the members of the peasantry group come from different age groups that influence their physical abilities, it is recommended to change the meeting schedule from the original one in the evening into the morning.